2015
DOI: 10.1016/j.bbmt.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Single and Multiple Dose MultiStem (Multipotent Adult Progenitor Cell) Therapy Prophylaxis of Acute Graft-versus-Host Disease in Myeloablative Allogeneic Hematopoietic Cell Transplantation: A Phase 1 Trial

Abstract: We conducted a multicenter, phase 1 dose escalation study evaluating the safety of the allogeneic multipotent adult progenitor cell (MAPC, MultiStem, Athersys, Inc., Cleveland, OH) stromal product administered as an adjunct therapy to 36 patients after myeloablative allogeneic hematopoietic cell transplantation (HCT). Patients received increasing doses of MAPC (1, 5, or 10 million cells per kilogram recipient weight) as a single i.v. dose on day +2 after HCT (n = 18), or once weekly for up to 5 doses (1 or 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 29 publications
1
56
0
Order By: Relevance
“…While clinical benefits were shown to be very minor and not of clinical value when MSCs were co-administered in haploidentical hematopoietic stem cell transplants for leukemia (Maziarz et al, 2015), the Athersys Multistem MSCs have shown some apparent benefit in reducing GVHD when used as adjunct therapy for myloablative allogeneic bone marrow cell transplants (Liu et al, 2011). However, purification of hematopoietic stem cells and, in particular, the removal of alloreactive T cells can probably accomplish this even more effectively (Logan et al, 2012;Shizuru et al, 1996).…”
Section: Mscsmentioning
confidence: 95%
“…While clinical benefits were shown to be very minor and not of clinical value when MSCs were co-administered in haploidentical hematopoietic stem cell transplants for leukemia (Maziarz et al, 2015), the Athersys Multistem MSCs have shown some apparent benefit in reducing GVHD when used as adjunct therapy for myloablative allogeneic bone marrow cell transplants (Liu et al, 2011). However, purification of hematopoietic stem cells and, in particular, the removal of alloreactive T cells can probably accomplish this even more effectively (Logan et al, 2012;Shizuru et al, 1996).…”
Section: Mscsmentioning
confidence: 95%
“…Because of the potent immunomodulatory and anti-inflammatory effects of MAPC cells and their capacity to enhance hematopoietic recovery following transplantation [16], we hypothesized that MAPC cells could be used as a novel therapy in MDS patients to decrease cytopenias because they might secrete factors that enhance hematopoiesis, reduce inflammation and/or replace defective niche cells.…”
Section: Introductionmentioning
confidence: 99%
“…These cells have extensive replication potential, are commercially available at clinical grade (Athersys Inc, Cleveland, Ohio) and are non‐immunogenic for alloreactive cytotoxic T lymphocyte induction, thus without potential adverse immune reactions . MAPCs have been approved for clinical studies in human patients with multiple disease indications including neurological, cardiovascular and inflammatory and immune diseases in the United States and Europe . Clinical‐grade human MAPCs are safe in human patients and effective on controlling human autoimmune disease and allograft rejection .…”
Section: Discussionmentioning
confidence: 99%